Registered nurses' job satisfaction in a New Zealand public hospital : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, Auckland, New Zealand - Beanlands, Philippa Jane (Massey University, 1999)
A multi-faceted questionnaire developed by Ng (1993) was used to explore registered nurses' job satisfaction in a major Auckland, New Zealand, public hospital. Participants (N = 123), were asked to complete the 24- item job satisfaction survey, and a questionnaire determining demographic and employment details. Analysis revealed 3 interpretable factors, Communication, Career Development, and Autonomy, compared with Ng's nation-wide study of 1988, which produced 7 factors. As expected, differences in nurses' job satisfaction appear to have occurred since Ng's study 11 years ago. These may be primarily attributable to the Health Reforms, which took place during the 1990's. Among the demographic and employment variables explored, gender was the only variable which showed any statistically significant effect. When the small number of male respondents (n =11) were matched to a similar number of females, differences were found in their responses to the Communication factor.
Appendix G: Computer programming and output of Data Analysis held on floppy disk with the print copy in Library.
Keywords: Auckland New Zealand Nurses; Job satisfaction; Nurses; Attitudes